Analisis Faktor Determinan Kejadian Suspek Tinea Kruris pada Santri Laki-laki - Mawarni, Imelda; Novrikasari, Novrikasari; Hartati, Yuli (Universitas Nurul Jadid, 2025)
Tinea cruris is a fungal skin infection that often occurs in tropical regions, including Indonesia, with a relatively high prevalence in dormitory environments such as Islamic boarding schools. This study aims to determine the determinants influencing the incidence of suspected tinea cruris in male students. This study used a quantitative method with a cross-sectional design, involving 224 male students at the Nurul Huda Tanah Merah Islamic Boarding School using a total sampling technique. Data were analyzed using univariate, bivariate, and multivariate analyses. The results of the regression analysis showed that personal hygiene and BMI were significantly associated with the incidence of tinea cruris. Personal hygiene was associated with a decrease in the incidence of tinea cruris, while BMI had a smaller effect. The regression model obtained proved significant, which means these factors have an important role in predicting the incidence of suspected tinea cruris. It can be concluded that poor personal hygiene and high BMI are the main factors contributing to the incidence of suspected tinea cruris in the Islamic boarding school environment. Therefore, the importance of hygiene interventions among students